Incidencia y prevalencia de depresión en estudiantes de ciencias de la salud de la UTP, 2003 - Cardona Giraldo, Dora; Tabima García, Diomedes; Mejía Ramírez, Ruby (Revista Médica de Risaralda, 2012)
No disponible en html.